A dynamic causality test of imports and economic growth in Zimbabwe. (1st January 2012) - Tsaurai, Kunofiwa
This study investigates the dynamic nexus between imports and economic growth in Zimbabwe using time-series data from 1980 to 2011. Three dominant views describe the relationship between imports and economic growth. The first view states that imports drives economic growth, the second view argues that it is economic growth that spurs imports expansion while the third view maintains that both imports and economic growth promote each other. The study employs the autoregressive distributed lag (ARDL)-bounds testing approach to examine the imports-growth linkage and error-correction-based causality test to capture both the short and long run dynamics. This study discovered a unidirectional causality relationship running from economic growth to imports – without any feedback in Zimbabwe in both short and long run. The study, therefore, recommends that Zimbabwe should pursue pro-economic growth policies and strategies in order to tap the benefits that come along with imports.